ASISTENSI PENANGANAN DAN PENCEGAHAN STUNTING DI DESA DAMARKASIYAN KECAMATAN KERTEK KABUPATEN WONOSOBO - Muhammad Saefullah; Robingun Suyud El Syam (Pusat Riset dan Inovasi Nasional, 2022)
Based on World Bank data, the stunting rate of the workforce in Indonesia reaches 54%, so it takes the role of all parties to succeed in the government's program to reduce the stunting rate. Through the assistance for handling and preventing stunting, the thematic Community Service Lecture (KPM) program based on the 2022 Al-Qur'an Science University in Damarkasiyan Village, it was concluded: that the assistance for stunting handling and prevention in Damarkasiyan Village was well received by the community. This activity raises awareness of citizens to live healthy and comply with recommendations from related parties.